A Modified Multiple Matching Method Based on Equipoise Pseudomulti-Channel Filter and Huber Norm (Communications in Computational Physics, 2020)
This study is aimed at improving multiple adaptive subtraction. We propose a modified pseudomulti-channel matching method based on the Huber norm, toadjust the matching differences on frequency and phase between the predicted multiples and original data. The second-order derivative of the predicted multiples is utilized to replace the derivative of its Hilbert transform. Due to the additional frequencyterm, this method can enhance the high-frequency component. We introduce 180〫 phase rotation of the multiple channels, which can decrease phase differences. TheHuber norm interpolates between smooth L2 norm treatment of small residuals androbust L1 norm treatment of large residuals. This method can eliminate the restrictionof large value conditions from the L2 norm and weaken the condition of orthogonalityfrom the L1 norm. The applications of the Pluto and Delft models shows that compared with pseudomulti-channel matching filter, the main frequency is increased from36 Hz to 38 Hz, and the primary reflection wave is more concentrated. The practicalapplication of field data verifies the effectiveness of the proposed method.
Keywords: Multiple; adaptive matching filter; equipoise pseudomulti-channel; Huber norm; second-order derivative.